Protective potency of clove oil and its transcriptional down-regulation of Aeromonas sobria virulence genes in African catfish (Clarias gariepinus L.) - Abd El-Hamid, M I; Abd El-Aziz, N K; Ali, H A (Cellular and Molecular Biology, 2016)
Disease episodes of fish caused by Aeromonas species are moved to the top list of limiting problems worldwide. The present study was planned to verify the in vitro antibacterial activities as well as the in vivo potential values of clove oil and ciprofloxacin against Aeromonas sobria in African catfish (Clarias gariepinus). The in vitro phenotypic virulence activities and the successful amplification of aerolysin and hemolysin genes in the precisely identified A. sobria strain were predictive for its virulence. In the in vivo assay, virulence of A. sobria strain was fully demonstrated based on constituent mRNA expression profile of tested virulence genes and typical septicemia associated with high mortalities of infected fish. Apparent lower mortality rates were correlated well with both decrescent bacterial burden and significant down-regulated transcripts of representative genes in the treated groups with clove oil, followed by ciprofloxacin as a prophylactic use for 15 days (P < 0.0001); however, the essential oil apart from ciprofloxacin significantly enhanced different hematological parameters (P < 0.05). In addition, administration of antibiotic may be considered as a pronounced stress factor in the fish even when it used in the prophylactic dose. In conclusion, medicinal plants-derived essential oils provide a virtually safer alternative to chemotherapeutics on fish, consumers and ecosystems.